Religion, Tradition, and Restorative Justice in Sierra Leone - Graybill, Lyn S. (Book collections on Project MUSE., 2017)
In this groundbreaking study of post-conflict Sierra Leone, Lyn Graybill examines the ways in which both religion and local tradition supported restorative justice initiatives such as the national Truth and Reconciliation Commission (TRC) and village-level Fambul Tok ceremonies.